A gene expression profiling approach assessing celecoxib in a randomized controlled trial in prostate cancer. - Sooriakumaran, P; Macanas-Pirard, P; Bucca, G; Henderson, A; Langley, SE; Laing, R; Smith, C; Laing, E; Coley, H (2009)
BACKGROUND: We performed a pilot study, looking at the COX-2 inhibitor celecoxib, on newly diagnosed prostate cancer patients in the neo-adjuvant setting using DNA microarray analysis. PATIENTS AND METHODS: This was a single-blinded, randomized controlled phase II presurgical (radical prostatectomy) 28-day trial of celecoxib versus no drug in patients with localized T1-2 N0 M0 prostate cancer. cDNA microarray analysis was carried out on prostate cancer biopsies taken from freshly obtained radical prostatectomy samples. Results were confirmed by qPCR analysis of a selection of genes. RESULTS: Multiple genes were differentially expressed in response to celecoxib treatment. Statistical analysis of microarray data indicated 24 genes were up-regulated and 4 genes down-regulated as a consequence of celecoxib treatment. Gene changes e.g. survivin, SRP72kDa, were associated with promoting apoptotic cell death, enhancement of antioxidant processes and tumour suppressor function (p73 and cyclin B1 up-regulation). CONCLUSION: Celecoxib at 400 mg b.i.d. for 4 weeks perioperatively gave rise to changes in gene expression in prostate cancer tissue consistent with enhancement of apoptosis and tumour suppressor function. Given the short time interval for the duration of this study, the data are encouraging and provide a good rationale for conducting further trials of celecoxib in prostate cancer.